Digitalization of Zakat Management from the Perspective of Contemporary Fiqh Muamalah - Muhammad Tajul ‘Arifin (Penerbit Yayasan Daarul Huda Kruengmane, 2026)
The development of digital technology has brought significant changes to various aspects of life, including zakat management as one of the important instruments in the Islamic economic system. The digitalization of zakat through online platforms, mobile applications, and electronic payment systems provides convenience for Muslims in fulfilling their zakat obligations quickly, transparently, and efficiently. This study aims to analyze the practices of digital zakat management and examine their compatibility with the principles of contemporary fiqh muamalah. The research employs a qualitative method with a normative approach and library research. Data were analyzed using a conceptual approach to the principles of fiqh muamalah related to transactions, trustworthiness (amanah), and public benefit (maslahah). The findings indicate that the digitalization of zakat management is fundamentally consistent with the principles of fiqh muamalah, provided that it fulfills the requirements of transparency, accountability, contractual clarity, and the absence of elements of gharar (uncertainty) and fraud. Furthermore, the use of digital technology in zakat management offers substantial opportunities to increase public participation and optimize the distribution of zakat to eligible beneficiaries (mustahik) more effectively. Therefore, digital zakat management can serve as an important innovation in the development of Islamic philanthropy while remaining grounded in Sharia principles.